استخدام كتاب العربية بين يديك بالمدخل الإتصالي بدار اللغة العربية بندا أتشيه - Basa, Ali; Afriati, Intan; Fadhilah, Fadhilah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Many factors influence the success of learning Arabic for non-native speakers. One of the textbooks is the Al-Arabiyyah Baina Yadaik book. Darul Lughah Al-Arabiyyah Banda Aceh uses this book in learning four language skills and their elements with a communicative approach. This research focuses on learning Arabic using the “Al-Arabiyyah Baina Yadaik” in Darul Lughah Al-Arabiyyah Banda Aceh. This research is descriptive, where the data is collected through interview and documentation. The resource persons in this study were the Director and one of the teachers at Darul Lughah Al-Arabiyyah Banda Aceh. The result shows that: The process Arabic teaching learning uses direct methods, where the teacher and students communication in Arabic, again the teacher encourages students to be involved in the Arabic learning process. In addition, The teacher is in use himself to speak Arabic with the student outside the classroom. The teacher explains the Arabic language skills learning material and its elements well and uses many exercises to master the materials being studied.